Geomorfologia do sistema sedimentar eólico de Paracaru - Ceará - Castro, João Wagner de Alencar (2001)
Study the origin and morphological evolution of the aeolian system associated to the Paracuru headland, with special emphasis in the active transversal dunes migration, identifying the main responsible agents for the coastal flats burying. The environmental factors: geology, pluvial precipitation, wind conditions, and waves climate, combined and associated to the geomorphologic classification, produced a set of information needed to understand the reply - process model proposed by this study. ln complementation to this analysis, the linking of ali collected information, obtained from geo-processing techniques and dune monitoring, established a better data integration, individualizing the proposed model in four well-defined cascading subsystems. This thesis work has included office, field and laboratory activities. Two sediment transportation directions were identified through this model. The first one is fed by the main direction of the east winds, and the second corresponds to the secondary direction of the southeast winds. Through the equation proposed by Simons et al. (1965), this study reveals that the total aeolian Transportation originated by the east winds towards Paracuru is estimated in 93,02 mª/m/year, while towards the sea (by southeast winds) is estimated in 37, 10 mª/m/year. Consequently, the material bulk transported towards the sea is approximately 1 /3 of the capacity of the one transported towards Paracuru town. With current wind conditions and pluvial precipitations maintained, part of Paracuru town will be buried by the dunes in a long-term basis, approximately 120 years.